From Aspirations to Loneliness: Why Female Early Career Researchers from Iran Choose to Leave Polish Academia - Amiri Ghadi, Nasim; Wadle, Hannah (Człowiek i Społeczeństwo, 2025)
This article discusses the lived experiences of female Iranian migrant early career researchers in Poland and their reasons for deciding to leave Poland and Polish Higher Education. It is based on biographical interviews conducted between 2023 and 2025. Juxtaposing the migrants’ aspirations and their experiences of social exclusions and systemic discriminations, the article portraits what it means to be a “minority minority” researcher in Poland’s higher education environment. While the researchers were largely content with the quality of higher education and the opportunities they had in research positions, they experienced a lack of welcoming culture in universities, everyday rejections as foreign nationals in urban life, and financial and legal, visa-related pressures. Commenting on the project of internationalizing research in Poland, the authors urge decisionmakers to take the experiences of Iranian female researchers seriously as a point of departure for re-thinking internationalization. They argue for an intersectional perspective that addresses multiple discriminations, while pointing at the specific responsibilities of universities for international researchers in Poland.